Qualitative Performance and Consumer Acceptability of Starch Films for the Blueberry Modified Atmosphere Packaging Storage - Giuggioli Nicole R.; Girgenti Vincenzo; Peano Cristiana (Polish Journal of Food and Nutrition Sciences)
The sustainability of packaging is an important part of food system innovation and it can influence the purchase decision for the fresh produce. In this work, we evaluated the qualitative performance and the consumer acceptability of three starch films for the blueberry modified atmosphere packaging (MAP) storage under fluctuating temperatures. Fruits cv. Duke were monitored for up to 18 days (15 days at 1±1°C and 3 days at 20±1°C). The respiration rate of the blueberries and the permeability of the films affect the initial atmospheric composition (0.2 kPa CO2 and 21.2 kPa O2) inside each package influencing the headspace gas composition and the quality parameters of the fruits. The F3 film has better controlled O2 values inside the packages up until the end of storage (5.7 kPa) and it maintained the highest anthocyanin content (156.21 mg C3G/100 g FW) and antioxidant capacity (22.18 Fe2+/kg) of fruits at 20±1°C.